If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + 8x = 5x + 4 Reorder the terms: 1 + 8x = 4 + 5x Solving 1 + 8x = 4 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 1 + 8x + -5x = 4 + 5x + -5x Combine like terms: 8x + -5x = 3x 1 + 3x = 4 + 5x + -5x Combine like terms: 5x + -5x = 0 1 + 3x = 4 + 0 1 + 3x = 4 Add '-1' to each side of the equation. 1 + -1 + 3x = 4 + -1 Combine like terms: 1 + -1 = 0 0 + 3x = 4 + -1 3x = 4 + -1 Combine like terms: 4 + -1 = 3 3x = 3 Divide each side by '3'. x = 1 Simplifying x = 1
| x^3+y^3=35 | | 6x-2(5+1x)=2(2x+1)-8 | | 1.7+7x=9.5-4x | | 7+2(m-5)= | | 8a+10=2(5-4a) | | Rw+8n=ar | | m(x)=8x | | -3(2x+5)+x=15 | | 6x-2(5x+1)=2(2x+1)-8 | | 4c-2c+15=25 | | d(5+3-2x)= | | 10x+8=5x+3+3(x+2) | | Rw+8n=a | | 5x+9=6x+4 | | 10x-24=18 | | 3c-4=-12 | | x=4x-25 | | 10+5(x+3)=50 | | 12-(x-3)=16 | | a^3-5a+6=a^2+3(a-1) | | x+3+4=60 | | 3c-4=12 | | (17n+11)-(9n+11)= | | 4=-9+y | | -6.3=0.9x | | (4y+3x-11)dx+(2x+y-5)dy=0 | | (j-1)(-3)= | | 1.7+7.6=9.5-4x | | 2=-9+y | | 5-(4x-3)=16 | | 2x+9-4x=-7+2x | | 0=-9+y |